PERENCANAAN SALURAN DRAINASE KAWASAN OASIS PT. DJARUM KUDUS DI KABUPATEN KUDUS - Ardianto Wibowo; Mohammad Yudhi Widyatmoko; Suseno Darsono; Sugiyanto Sugiyanto (Jurnal Karya Teknik Sipil, 2014)
Drainage problems, especially in the cities of Indonesia has become important with the frequent occurrence of  flooding or water logging in the rainy season at urban areas that disrupt people life and obstruct transportations fluency and cause property losses in large enough quantities. The main cause of flooding or water logging is a change from the natural landscape into the development environment, hence, increasing impermeable surfaces, such as roads, parking areas, sidewalks, and residential areas. This change reduces, disrupts, or eliminates the natural vegetation, land surface, basin, and natural drainage pattern that prevents, vaporizes, stores, issues slowly and absorbs the rainwater. The impact of changes in the landscape of OASIS Area of PT. Djarum Kudus is the increasing direct runoff (run off) while reducing water seep into the ground so that it can make the puddle of water. In its planning, the hydrologic analysis using the 15 years of rainfall data in Sta. Kedung Gupit is performed. In hydrologic analysis of this planning is applied the probability distributions of Log Pearson type 3 and is used EPA SWMM program with 10-years return period of flooding, thus, it is obtained the maximum flood discharge before construction in the amount of 9.05 m3/second and the maximum flood discharge after development in the amount of 16.69 m3/second. Based on the results of that analysis, the planning of drainage canals is carried out. In the planning, the used drainage canals are new drainage canals which are constructed at the OASIS area of PT. Djarum Kudus. The dimensions of the drainage canals that are used vary from the largest with the dimension of 2.5 m x 3 m and the smallest with the dimension of 0.6 m x 0.6 m. Furthermore, to determine the effectiveness of the drainage canals, it is modeled using HEC RAS program. In the calculations using that program, all the canals that are planned in the OASIS area of PT. Djarum are currently able to accommodate water during the flooding for return period plan of 10 years. Planning areas OASIS Drainage System PT. Djarum Kudus produces The dimensions of the drainage canals that are the largest with the dimension of 2.5 m x 3 m and the smallest with the dimension of 0.6 m x 0.6 m. The construction of drainage canals at OASIS area of PT. Djarum Kudus takes time for 4 months with a total cost incurred is 9,490,131,000.00 (nine billion four hundred and ninety million one hundred and thirty-one thousand rupiahs).